Size matters: Entrepreneurial entry and government - Ruta Aidis; Saul Estrin; Tomasz Mickiewicz (Institute for the Study of Labor (IZA), 2010)
We explore the country-specific institutional characteristics likely to influence an individual's decision to become an entrepreneur. We focus on the size of the government, on freedom from corruption, and on 'market freedom' defined as a cluster of variables related to protection of property rights and regulation. We test these relationships by combining country-level institutional indicators for 47 countries with working age population survey data taken from the Global Entrepreneurship Monitor. Our results indicate that entrepreneurial entry is inversely related to the size of the government, and more weakly to the extent of corruption. A cluster of institutional indicators representing 'market freedom' is only significant in some specifications. Freedom from corruption is significantly related to entrepreneurial entry, especially when the richest countries are removed from the sample but unlike the size of government, the results on corruption are not confirmed by country-level fixed effects models.
Keywords: L26; P14; P51; P37; 330; Entrepreneurship; government; market freedom; corruption; Unternehmer; Unternehmensgründung; Markteintritt; Institutionelle Infrastruktur; Staatsquote; Korruption; Wirtschaftsliberalismus; Schätzung; Welt